Reading Fluency and its Relationship with Comprehension: A Systematic Literature Review - Amanda Oliveira Meggiato; Helena Vellinho Corso; Luciana Vellinho Corso (Paidéia (Ribeirão Preto))
Abstract: Research on reading fluency variably emphasizes accuracy, automaticity and prosody, without clarifying the direction of its relationship with comprehension. This systematic review aimed to examine the scientific production on the definition of fluency and its relationship with reading comprehension from the perspective of cognitive psychology. Following PRISMA guidelines, the phases of identification, selection, eligibility, inclusion and data extraction were conducted. A search in databases such as Web of Science, SciELO, American Psychological Association, among others, resulted in the inclusion of 57 studies. The synthesis revealed that 60% of the researches define fluency as accuracy, automaticity and prosody, identifying it as a predictor of comprehension (81%). In terms of evaluation, accuracy and speed measures are the most used (58%), while prosody remains neglected. It is concluded that advances in the definition of fluency are crucial. This review provides a better understanding of the construct, contributing to teaching and assessment practices.